Three‐dimensional organotypic culture of human salivary glands: the slice culture model. (4th July 2016) - Su, X; Fang, D; Liu, Y; Ramamoorthi, M; Zeitouni, A; Chen, W; Tran, SD
Abstract : Objective: A challenge in studying human salivary glands is to maintain the cells ex vivo in their three‐dimensional (3D) morphology with an intact native extracellular matrix (ECM) environment. This paper established a human salivary 3D organotypic slice culture model that could maintain its physiological functions as well as allowing a direct visualization of the cells. Methods: Human salivary biopsies from six patients were embedded in agarose and submerged in cold buffer for thin (50 μ m) sectioning using a vibratome. 'Salivary slices' were mechanically supported by a porous membrane insert that allowed an air–liquid interface and cultured in serum‐free culture media. Cell viability, proliferation, apoptosis, physiological functions, and gene expression were assessed during 14 days of culture. Results: Human salivary slices maintained cell survival (70–40%) and proliferation (6–17%) for 14 days ex vivo . The protein secretory (amylase) function decreased, but fluid (intracellular calcium mobilization) function was maintained. Acinar, ductal, and myoepithelial cell populations survived and maintained their 3D organization within the slice culture model. Conclusion: The human salivary slice culture model kept cells alive ex vivo for 14 days as well as maintaining their 3D morphology and physiological functions.